2006
DOI: 10.1159/000096713
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Speech Perception, Self-Rated Tinnitus Loudness and Disability in Tinnitus Patients with Normal Pure-Tone Thresholds of Hearing

Abstract: Exactly how speech perception and tinnitus perception are related remains unclear. This study investigated how tinnitus alone affects speech perception and the relationship between speech perception, tinnitus loudness, and tinnitus disability. The Mandarin Speech Perception in Noise Test (MSPIN), Tinnitus Loudness Scaling (TLS), and Tinnitus Handicap Inventory (THI) were utilized to assess 20 tinnitus patients with normal hearing. The tinnitus group had a significantly lower MSPIN score than the control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
19
3
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 29 publications
10
19
3
10
Order By: Relevance
“…Previous studies showed that speech discrimination was mostly affected in TP in noisy environment which was not the case in the present study (Spitzer et al, 1983;Huang et al, 2007;Ryu et al, 2012). In addition, the two French words "gauche" (left) and "droite" (right) that were used in the word recognition condition sounded clearly differently, which should have facilitated their discrimination.…”
Section: Slowed Down Processing Speed In Tinnituscontrasting
confidence: 44%
“…Previous studies showed that speech discrimination was mostly affected in TP in noisy environment which was not the case in the present study (Spitzer et al, 1983;Huang et al, 2007;Ryu et al, 2012). In addition, the two French words "gauche" (left) and "droite" (right) that were used in the word recognition condition sounded clearly differently, which should have facilitated their discrimination.…”
Section: Slowed Down Processing Speed In Tinnituscontrasting
confidence: 44%
“…Similar to Newman et al (1994), Goldstein and Shulman stressed the contribution of central processes to the generation of chronic tinnitus. Huang et al (2007) investigated speech perception in 20 chronic tinnitus patients speaking Mandarin. Compared to controls, tinnitus patients displayed generally lower scores in perceiving sentences in noise and, as it appears (though it was not analyzed), this was more so when sentences were hard to predict, i.e., with low contextual cues.…”
Section: Resultsmentioning
confidence: 99%
“…We are aware that there may be a selection bias as the sample comes from a tertiary referral clinic. However, our sample is much larger than previously investigated samples (Huang et al, 2007) and consisted of unselected patients who consecutively presented because of tinnitus in our clinic. Moreover, there are similar reports of high prevalence of speech intelligibility deficits in workers with exposure to noise and tinnitus (Soalheiro et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of a large sample of 495 workers who suffered from tinnitus showed speech intelligibility deficits as compared to workers without tinnitus (Soalheiro et al, 2012). A small study investigating 20 Chinese speaking patients with tinnitus revealed that speech comprehension was impaired as compared to a control group, particularly in noisy environments (Huang et al, 2007). Another study revealed that masking of tinnitus by sound improved speech comprehension (Ryu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%